1978
DOI: 10.1104/pp.61.1.107
|View full text |Cite
|
Sign up to set email alerts
|

Cucumber Seedling Indoleacetaldehyde Oxidase

Abstract: Extracts of light-grown Cucumis sativus L. seedlings catalyzed the oxidation of indole-3-acetaldehyde to indole-3-acetic acid. No added cofactors were required. Inhibitor studies indicated that the enzyme is a metafloflavoprotein. While indole-3-aldehyde, benzaldehyde, and phenylacetaldehyde partially inhibited the oxidation of indole-3-acetaldehyde, suggesting that they may serve as alternative substrates, it is proposed that indoleacetaldehyde is the major substrate in vivo. 2,4-Dichlorophenoxyacetic acid st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

1978
1978
2002
2002

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 4 publications
1
28
0
Order By: Relevance
“…The data are plotted by the LineweaverBurk method; nonlinear plots are indicative of nonhyperbolic kinetics, and concave plots ( Possible Roles for IAAld Reductase in the Regulation of Auxin Biosynthesis. We have reported that IAA is a potent inhibitor of highly purified IEt oxidase (10), and experiments with a crude preparation of IAAld oxidase activity from cucumber seedlings have shown that this activity is inhibited by 2,4-D, a chemical analog of IAA (2). These results suggest that IAA regulates its own synthesis through feedback inhibition of the terminal enzyme of the pathway.…”
Section: Methodsmentioning
confidence: 68%
See 1 more Smart Citation
“…The data are plotted by the LineweaverBurk method; nonlinear plots are indicative of nonhyperbolic kinetics, and concave plots ( Possible Roles for IAAld Reductase in the Regulation of Auxin Biosynthesis. We have reported that IAA is a potent inhibitor of highly purified IEt oxidase (10), and experiments with a crude preparation of IAAld oxidase activity from cucumber seedlings have shown that this activity is inhibited by 2,4-D, a chemical analog of IAA (2). These results suggest that IAA regulates its own synthesis through feedback inhibition of the terminal enzyme of the pathway.…”
Section: Methodsmentioning
confidence: 68%
“…The (100%) control rate was 39 nmol NADPH oxidized per min per ml enzyme. Controls have shown that the difference in ionic strength between, for example, 2 Figure 2 shows the reaction kinetics of the NADH-linked IAAld reductase activity. The Lineweaver-Burk plots indicate a sequential mechanism (both substrates add to the enzyme before any product dissociates) and are consistent with either random or ordered addition of the substrates.…”
Section: Methodsmentioning
confidence: 99%
“…Some of these are directly involved in the metabolism of indole-3-acetaldehyde. They include three amine oxidases which can oxidize tryptamine to IAAld4 (7), an indoleethanol oxidase which oxidizes indole-3-ethanol to IAAld (8,13), IAAld reductases which reduce IAAld to IEt (1,3), and an IAAld oxidase which oxidizes IAAld to IAA (2). These demonstrations could be considered irrelevant to the actual biosynthesis of auxin unless it is shown that IAAld occurs naturally in the cucumber seedling.…”
mentioning
confidence: 99%
“…Under the assumption that at least under some physiological conditions IAAld' may be a major precursor of IAA (formed either from indole-3-acetaldoxime [12], tryptamine, or indole-3-pyruvic acid [27]), the reversible oxidation-reduction of the aldehyde to IEt by IAAld reductase may reduce the rate of IAA biosynthesis and thus IAA concentration (4,27). Upon changing physiological conditions lEt may be 'reactivated' by oxidation to IAAld and IAA via lEt oxidase (23) and IAAld oxidase (3).…”
mentioning
confidence: 99%